Neck Circumference and Cardiovascular Outcomes: Insights From the Jackson Heart Study - Pumill, Christopher A. (Am Heart J, 2019)
BACKGROUND: Emerging data suggest that neck circumference (NC) is associated with cardiometabolic risk factors. Limited research is available regarding the association between NC and cardiovascular outcomes in African Americans. METHODS: Using data from the Jackson Heart Study, we included participants with recorded NC measurements at baseline (2000–2004). Baseline characteristics for the included population were summarized by tertiles of NC. We then calculated age- and sex-adjusted cumulative incidence of clinical cardiovascular outcomes and performed Cox proportional hazards with stepwise models. RESULTS: Overall, 5290 participants were categorized into tertiles of baseline NC defined as ≤37 cm (N=2179), 38–40 cm (N=1552), and >40 cm (N=1559). After adjusting for age and sex, increasing NC was associated with increased risk of heart failure (HF) hospitalization (cumulative incidence = 13.4% [99% CI, 10.7–16.7] in the largest NC tertile vs. 6.5% [99% CI, 4.7–8.8] in the smallest NC tertile), but not mortality, stroke, myocardial infarction or coronary heart disease (all P≥0.1). Following full risk adjustment, there was a nominal increase in the risk of HF hospitalization with increasing NC, but this was not statistically significant (hazard ratio per 1-cm increase, 1.04 [99% CI, 0.99–1.10], P=0.06). CONCLUSIONS: In this large cohort of African American individuals, a larger NC was associated with increased risk for HF hospitalization following adjustment for age and sex, but this risk was not statistically significant after adjusting for other clinical variables. Although NC is not independently associated with increased risk for cardiovascular events, it may offer prognostic information particularly related to HF hospitalization.